THE TAXATION OF COOPERATIVES.A PROPOSAL FOR ITS UNIFORM REGULATION IN CUBA - Musa, C. Orestes Rodríguez; Aguilar, C. Orisel Hernández; Otero, Liana Simon (International Journal of Cooperative Law, 2025)
Thepromulgation of the Constitutionof the Republic of Cuba of 2019 supposed the general recognition of the cooperative, overcoming the past distinctions between its differentforms and laying down some guidelines for the determination of its legal nature inthesocioeconomic system of the country. At the level of ordinary development laws, including legal provisions on tax matters, a full reflection of this transformation has not yet been achieved. Consequently, the objective assumed in this work seeks to argue the premises that should guide the unification of the tax regime of Cuban cooperatives, in accordance with the role constitutionally assigned to them and their identity.